Scenario analysis of energy system transition - A case study of two coastal metropolitan regions, eastern China. (November 2019) - Xiao, Mengzhu; Simon, Sonja; Pregger, Thomas
Abstract: The scenario analysis focuses on two metropolitan regions of eastern China which are characterized by high energy consumption and related CO2 emissions. Current policies are rather short-term driven and weak regarding sectoral coupling and regional integration. As in China economic activities and population on the one hand and renewable energy resources on the other have a very imbalanced distribution, long-term integrated energy system modelling needs to consider specific regional challenges of efficiency improvement, coal reduction, transport decarbonization and multi-sector electrification. Three scenarios are constructed, namely a Current Policy Scenario (CPS), Natural Gas & Nuclear Scenario (NGNS) and Renewable & Import Scenario (RIS) based on a normative storyline-and-modelling approach. The simulation results show that regional CO2 emissions could be significantly reduced in all sectors with the adjustment of economic structure, adopted efficiency measures, fuels to replace coal and oil products and multi-sector electrification supported by enhanced power import capacity. The scenario analysis provides insights for a strategic implementation of long-term integrated energy transition options towards decarbonization for metropolitan regions both from supply and demand sides. Highlights: Fill the gap between short-term policies and long-term transition pathways. Scenario analysis of integrated energy system transition in metropolitan regions. Strategic implementation of decarbonization options to deal with regional challenges. Policy advice for regional energy system transition from long-term perspectives.